Mucosal associated invariant T cells in pulmonary tissue repair - Zhang, X (2024)
Mucosal-associated invariant T (MAIT) cells are the most abundant unconventional T cells in the lung and can respond to bacterial, fungal, and viral challenges. We and others have recently described a potential role in promoting tissue repair. However, it is unknown what role MAIT cells play during sterile lung tissue damage.